The Effects of Environmental Sound and Animation on the Naming Accuracy of Graphic Symbols. - Brock, Kris L.; Aldrich, Sarah; Ogiela, Diane A.; Eller, Amanda; Gallup, Jenn (Perspectives of the ASHA Special Interest Groups, 2024)
Purpose: The purpose of this study is to systematically replicate and extend previous research by examining the effect of symbol format (sound and no sound) on naming accuracy across twenty-eight 4-year-old participants. COVID-19 social distancing requirements introduced a new variable called experimental modality because half of the participants completed this study face-to-face while the other half completed this study through telepractice. Method: A 2 x 2 mixed measures analysis of variance was conducted. Symbol format was the within-subject variable while experimental modality was the between-subjects variable. Symbol error analysis was also conducted to improve symbol creation. Results: Sound did not significantly enhance the naming accuracy of verb symbols. The experimental modality had no significant effects either. Conclusions: Results were inconsistent with previous research, suggesting that the inclusion of sound may only be beneficial with younger children and with certain symbols that have not been mastered. Clinicians should use animation and sound as multimedia learning tools on a case-by-case basis. Based on results from this study, researchers may wish to consider teleresearch to increase sample size for similar studies.